Intermedial Transformation in Comic Book Movie Adaptation of X-Men: First Class (NOBEL: Journal of Literature and Language Teaching, 2020)
The objects of this study are eight X-Men: First Classcomic books, volume 1 published from September 2006 until April 2007 andX-Men: First Classmovie made in 2011.Texts in the forms of dialogues and visual images taken both from the comic books and the movie are the data which then are analysed qualitatively. Applying intersemiotic translation promoted by Zecca, this study is trying to uncover how social and economic factors influence translation process and whether there are any continuity and changes along the process. The study focuses on the social and economic aspects involved in the process of transforming X-Men: First Class comic books as the source text, into the movie version as the targeted texts. Some adaptation and changes occurred as the consequence; plot and story lines are twisted, characters involved are replaced for the purpose of meeting the expectation of the targeted market of the movie. Supported by those who were involved in the process and the social issues echoing at the time when the process is happening, the social issues depicted in the texts are also sifted.